Determinants of Household Savings - Sahudin, Zahariah; Ridzuan, Abdul Rahim; Razak, Mohamad Idham Md; Bahrudin, Nur Zahidah (Advances in Social Sciences Research Journal, 2024)
The household savings growth in Malaysia has shown a great declining trend annually. The main causes of these deteriorating patterns could have been due to low-income levels, overspending, economic conditions as well as uncertainties that people are facing daily. In deliberating this issue further, this study has empirically examined factors affecting household savings in Malaysia. The analysis was based on time-series data gathered from World Bank Data and the Department of Statistics of Malaysia from 1970 until 2020. The time series regression analysis was used to examine the significant influence on the dependent variable, savings, by independent variables, which consist of income level, interest rate, and money supply. The findings from this study revealed that income level and money supply have significant positive influences on savings, while interest rate has an insignificant influence on savings. Through these findings, policymakers have to formulate a suitable policy that can cushion the impact of macroeconomic variables on the level of savings in the country.